Fragmentation of patient safety research: a critical reflection of current human factors approaches to patient handover - Tanja Manser (SAGE Publishing, 2013)
The integration of human factors science in research and interventions aimed at increased patient safety has led to considerable improvements. However, some challenges to patient safety persist and may require human factors experts to critically reflect upon their predominant approaches to research and improvement. This paper is a call to start a discussion of these issues in the area of patient handover. Briefly reviewing recent handover research shows that while these studies have provided valuable insights into the communication practices for a range of handover situations, the predominant research strategy of studying isolated handover episodes replicates the very problem of fragmentation of care that the studies aim to overcome. Thus, there seems to be a need for a patient-centred approach to handover research that aims to investigate the interdependencies of handover episodes during a series of transitions occurring along the care path. Such an approach may contribute to novel insights and help to increase the effectiveness and sustainability of interventions to improve handover.